CAKRA RADIO AS A DIVERSIFICATION FORM OF ARDAN GROUP - Fathurrahman, Donny; Gissani, Muhammad Fikri; Nugraha, Adhyasa Henry (TOPLAMA, 2024)
Ardan Group utilizes a three-pronged diversification strategy: concentric, horizontal, and conglomerate. Notably, Cakra Radio and Ardan Hotel exemplify this approach.  Cakra Radio, focusing on local culture, integrates itself into the lives of Bandung residents. Through diverse programming and high-quality content, it strives to remain the city's preferred radio station. Ardan Hotel, on the other hand, represents horizontal diversification. By entering the hospitality industry, Ardan Group expands into a related but distinct sector. The hotel caters to guests seeking an exclusive experience with top-notch facilities and services. Its success hinges not only on luxurious accommodations but also on efficient and innovative management practices. This demonstrates Ardan Group's ability to adapt and thrive in a dynamic business environment. In essence, Ardan Group's diversification strategy, exemplified by Cakra Radio and Ardan Hotel, fosters comprehensive growth. By strategically expanding into various sectors, the group optimizes its potential while managing risks. This approach has propelled them to success not only in radio but also in the hospitality industry.